Medicine and practical ethics in Galen - Xenophontos, Sophia A., 1985- (Cambridge ; New York, NY : Cambridge University Press, 2024)
Galen was notable in the ancient world for his creative intermingling of medicine and practical ethics. This book is the first authoritative analysis of Galen's psychological and ethical works alongside a large number of his technical tracts, both medical and philosophical, and offers a robust framework through which we can comprehend his role as a practical ethicist - an aspect of his intellectual profile that has been little understood until now. Sophia Xenophontos explores a wide range of literature on moralia in the Roman imperial period, as well as topics including the pathology of emotions, the social role of medicine, and character formation and social ethics, to show the sophisticated and complex ways in which moral themes and controversies from antiquity were adapted and reinvigorated by Galen. This title is also available as Open Access on Cambridge Core.
Introduction: Galen, the unsuspected moralist -- General protreptic and suggested approaches to life -- Practical ethics in technical accounts -- Moral medicine -- Avoiding distress -- Exhortation to the study of medicine -- Affections and errors of the soul -- Recognising the best physician -- Prognosis.
Title from publisher's bibliographic system (viewed on 15 Dec 2023).
Keywords: Galen -- Criticism and interpretation; Medical ethics -- Greece; Medicine, Greek and Roman